Welfare implications for broiler chickens reared in an insect larvae-enriched environment: Focus on bird behaviour, plumage status, leg health, and excreta corticosterone - Biasato, Ilaria; Bellezza Oddon, Sara; Chemello, Giulia; Gariglio, Marta; Fiorilla, Edoardo; Dabbou, Sihem; Pipan, Miha; Dekleva, Dominik; Macchi, Elisabetta; Gasco, Laura; Schiavone, Achille (Frontiers in Physiology, 2022)
The use of insect live larvae as environmental enrichment has recently been proposed in broiler chickens, but the concomitant administration of black soldier fly (BSF) and yellow mealworm (YM) has never been tested yet. Therefore, the present study aims to evaluate the effects of live BSF and YM larvae as environmental enrichments for broiler chickens by means of plumage status, behaviour, leg health, and excreta corticosterone metabolites (CM). A total of 180 4-day old male Ross 308 broiler chickens were randomly distributed in 3 experimental treatments (6 replicates/treatment, 10 birds/replicate) and fed for 35 days as follows: 1) control (C, commercial feed), 2) BSF: C + 5% of the expected daily feed intake [DFI] live BSF larvae and 3) YM: C + 5% of the expected DFI live YM larvae. Feathering, hock burn (HB) and footpad dermatitis (FPD) scores (end of the trial), as well as behavioural observations (beginning of the trial [T0] and every 11 days [T1, T2 and T3] during morning, larvae intake and afternoon) through video recordings, were assessed, and excreta samples collected to evaluate the CM. Feathering, HB and FPD scores, and excreta CM were unaffected by insect live larvae administration (p > 0.05). In the morning, the insect-fed birds displayed higher stretching, wing flapping, ground pecking (at T1 and T3), as well as lower preening (at T1 and T2), than the C group (p < 0.05). During the larvae intake, higher scratching, wing flapping and ground pecking, as well as lower stretching, preening and laying down, were observed in the insect-fed (scratching, stretching and laying down) or YM-fed (wing flapping, ground pecking and preening) groups than the C birds (p < 0.05). In the afternoon, insect live larvae administration increased wing flapping (YM) and laying down (BSF and YM), as well as decreased ground pecking (YM, p < 0.05). In conclusion, the administration of insect live larvae as environmental enrichment (especially YM) was capable of positively influencing the bird welfare through the stimulation of foraging behaviour, increase in activity levels, and reduction in bird frustration, without affecting the plumage status, leg health, and excreta CM.